Advancing Particle Technology Research in Indonesia: Insights from Computational Bibliometric Analysis - Kurniawan, Tedi; Nandiyanto, Asep Bayu Dani (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2023)
This study explored the progress and trends in particle technology research in Indonesia using computational bibliometric analysis based on the Scopus database. Examining academic publications, collaboration networks, and citation patterns identified key areas of focus, influential contributors, and emerging topics within the field. Insights gained from this study provide a comprehensive overview of the research landscape, highlighting Indonesia's contributions to particle technology and offering guidance for future research priorities and collaborations. The findings aim to strengthen the country's scientific presence in this domain and foster innovation and global engagement